Subject verb agreement errors in essay writing among Diploma in Culinary Arts Students in UiTM Dungun, Terengganu / Najlaa' Nasuha Mohd Radin and Lee Lai Fong - Mohd Radin, Najlaa' Nasuha; Lee, Lai Fong (ACRULeT, Faculty of Education & UiTM Press, 2012)
This study investigated errors in subject verb agreement in the writing of Diploma in Culinary Arts students in UiTM Dungun, Terengganu. 15 students were selected as the sample and 45 essays were collected from them for data analysis. The data collected were analyzed using SPSS software version 18. The findings indicated that the students had problems in four types of subject verb agreement which were subject verb agreement for person, subject verb agreement of number, subject verb agreement of indefinite subject and subject verb agreement of notional agreement and proximity but no error was found for subject verb agreement of coordinated subjects. The students were also found to have problems mostly with subject verb agreement of number, followed by notional agreement and proximity, subject verb agreement of person and subject verb agreement of indefinite subject. This implies that students have problems in different types of subject verb agreement in their writing and the current teaching strategies should be revisited by language instructors to help the diploma students improve in their use of SVA in their writing.